Φ-Prime and ϕ-Primary Elements in Multiplicative Lattices. (9th October 2014) - Manjarekar, C. S.; Bingi, A. V.
Abstract : We investigate ϕ -prime and ϕ -primary elements in a compactly generated multiplicative lattice L . By a counterexample, it is shown that a ϕ -primary element in L need not be primary. Some characterizations of ϕ -primary and ϕ -prime elements in L are obtained. Finally, some results for almost prime and almost primary elements in L with characterizations are obtained.